Association of UCP‐3 rs1626521 with obesity and stomach functions in humans. (7th March 2015) - Acosta, Andres; Camilleri, Michael; Shin, Andrea; Vazquez‐Roque, Maria I.; Iturrino, Johanna; Lanza, Ian R.; Nair, K. Sreekumaran; Burton, Duane; O'Neill, Jessica; Eckert, Deborah; Carlson, Paula; Vella, Adrian; et al.
Abstract : Objective: To examine the association of gene variants of uncoupling proteins (UCP) ‐2 and −3 with obesity and gastrointestinal (GI) traits. Methods: In 255 overweight or obese adults, the associations of gene variants in UCP‐2 (−3474, rs659366) and UCP‐3 (rs1626521, rs2075577, rs15763) with body weight (BW) and GI traits were studied. Gene variants were genotyped by TaqMan® assay. The associations of genotypes with BW and GI traits (gastric emptying, gastric volume, satiety by buffet meal, satiation by nutrient drink test and GI hormones) were assessed using ANOVA corrected for false detection rate (FDR). Results: A novel UCP‐3 gene variant, rs1626521, was identified; it was associated with BW ( P = 0.039), waist circumference ( P = 0.035), and significantly higher postprandial gastric volume ( P = 0.003) and calories ingested at buffet meal ( P = 0.006, both significant with FDR). In a subgroup of 11 participants, rs1626521 was also associated with reduced mitochondrial bioenergetics efficiency in skeletal muscle ( P = 0.051). In an in vitro study in HEK293 cells, rs1626521 reduced UCP‐3 protein expression ( P = 0.049). Associations detected between other genotypes and GI traits were nonsignificant with FDR. Conclusions: A newly identified functional variant (rs1626521) in UCP‐3 affects postprandial gastric functions and satiety and may contribute to weight gain and alter human mitochondrial function.